Pengaruh Kompensasi Terhadap Motivasi Kerja Karyawan Pada CV Satu Atap Communication Medan - Lumbanraja, Esha Junita Br; Jumjuma, Jumjuma (Abdimas Indonesian Journal, 2024)
Compensation is the most important thing that must be considered by the company with compensation, it will increase employee motivation. It can be seen that compensation is something that is received by employees in return for their services to the company in the form of salaries, allowances, incentives, and facilities. Work motivation is a condition that encourages or causes someone to do something or an activity that takes place consciously and aims to improve work performance. With good motivation, every employee who does the job will be excited and happy to do the job, so that the higher the enthusiasm and drive to work. This study aims to determine how compensation partially and simultaneously affects employee work motivation at CV Satu Atap Communication Medan. The population and sample in this study were 30 employees with saturated sample technique. Data collection techniques through observation and questionnaire distribution. The data analysis technique used is the Multiple Linear Regression analysis method. Partial test results for the salary variable (X1) obtained tcount> ttable (2.290> 1.708) with a significance value smaller than the 0.05 level (0.031 <0.05), this means that salary (X1) has a positive and significant effect on work motivation (Y). For the allowance variable (X2), it is obtained tcount> ttable (2.419> 1.708) with a significance value smaller than the 0.05 level (0.031<0.05), this means that salary (X1) has a positive and significant effect on work motivation (Y). With a fairly high level of determination, indicated by an adjusted R-square of 0.626. This value shows that salary, allowances, incentives and facilities contribute 62.2% to the work motivation of CV Satu Atap Communication Medan employees. While the remaining 37.4% is influenced by other variables not examined by this study.